2013
DOI: 10.7860/jcdr/2013/5091.2794
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteriology of Diabetic Foot Ulcers, with a Special Reference to Multidrug Resistant Strains

Abstract: Introduction: A diabetic foot infection is one of the most feared complications of Diabetes mellitus. Many studies have reported on the bacteriology of Diabetic Foot Infections (DFIs) over the past 25 years, but the results have been varied and often contradictory. Aims and Objectives:This study was carried out to determine the bacterial profiles of infected ulcers and the antibiotic resistance pattern of the isolates. Materials and Methods:Samples were collected from 50 patients with diabetic foot ulcers by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
77
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 10 publications
19
77
0
4
Order By: Relevance
“…The percentage of ciprofloxacin and gentamicin resistant E.coli were 60.53%, 52.63% respectively. All the 38 (100%) isolates were sensitive to imipenem and is in concordant with these following studies, Varaiya et al, (2008), Bansal et al, (2008) and Shanmugam et al, (2013).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The percentage of ciprofloxacin and gentamicin resistant E.coli were 60.53%, 52.63% respectively. All the 38 (100%) isolates were sensitive to imipenem and is in concordant with these following studies, Varaiya et al, (2008), Bansal et al, (2008) and Shanmugam et al, (2013).…”
Section: Resultssupporting
confidence: 78%
“…Many studies in India had reported aerobic gram negative bacillary organisms to be more predominant in diabetic foot ulcer infection than aerobic gram positive cocci (Shankar et al, 2005;Bansal et al, 2008;Shanmugam et al, 2013;Gadepalli et al, 2006;Swarna et al, 2012). Out of 173 organisms isolated 118 (68%) were gram negative bacilli and 55 (32%) were gram positive cocci in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fidelis Mbunda et al [9] and Lim et al [10] reported similar results. Priyadarshini Shanmugam, Jeya M, and Linda Susan S stated that the commonest isolate was Pseudomonas spp (16%) [18]. These findings also correlate well with those of Pappu K et al [19], who reported that 76% of the organisms which were isolated were gram negative bacilli, Pseudomonas being the predominant pathogen (23%), followed by Staphylococcus aureus (21%).…”
Section: Discussionsupporting
confidence: 80%
“…Diabetic foot is characterized by sensory, motor and autonomic neuropathy and peripheral vascular disease, which may lead to the development of ulceration, infection and gangrene (2). The ultimate outcome of diabetic foot is amputation, which is associated with relatively high morbidity and mortality (3).…”
Section: Introductionmentioning
confidence: 99%